2020
DOI: 10.1001/jamadermatol.2019.4912
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Dermoscopic Features Associated With Difficult-to-Recognize Variants of Cutaneous Melanoma

Abstract: The clinical and dermoscopic features of the vast majority of uncommon variants of cutaneous melanoma have been rarely reported, leading to difficulty in making accurate diagnoses.OBJECTIVE To define the main clinical and dermoscopic features of the most frequently reported but uncommon histologic variants of cutaneous melanoma.EVIDENCE REVIEW A 2-step systematic review of the literature was performed (from inception to November 2018) using PubMed, Embase, and Cochrane Central Register of Controlled Trials dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 105 publications
1
25
0
Order By: Relevance
“…These kinds of cells are described not only in benign nevi including Spitz, combined halo, dysplastic, nodal, and blue nevi, [12][13][14][15][16] but also in malignant lesions, such as in melanoma of the skin, choroid, or conjunctiva. 3,[17][18][19] No clinical features are suspect to the diagnosis, and single case reports are described in the literature showing different In our cases, each BCN was a smooth brownish macular lesion, confirming the aspect of common nevus reported in the literature. The most common location reported is the head and neck area.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These kinds of cells are described not only in benign nevi including Spitz, combined halo, dysplastic, nodal, and blue nevi, [12][13][14][15][16] but also in malignant lesions, such as in melanoma of the skin, choroid, or conjunctiva. 3,[17][18][19] No clinical features are suspect to the diagnosis, and single case reports are described in the literature showing different In our cases, each BCN was a smooth brownish macular lesion, confirming the aspect of common nevus reported in the literature. The most common location reported is the head and neck area.…”
Section: Discussionsupporting
confidence: 83%
“…Ballooning cell changes would be caused by an arrest of biosynthesis of melanin and would reflect an intrinsic cellular degenerative process, resulting in less pigmented than typical melanocytes. These kinds of cells are described not only in benign nevi including Spitz, combined halo, dysplastic, nodal, and blue nevi, 12–16 but also in malignant lesions, such as in melanoma of the skin, choroid, or conjunctiva 3,17–19 …”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of change as a concerning feature of malignancy, 5 it is only natural that this PG pattern may induce anxiety among dermoscopists. To complicate matters, PGs have also been seen in melanoma, especially follicular and naevoid melanoma 6 . In fact, studies have found different frequencies of melanomas among PG lesions, ranging from 0 to 28% 7–9 …”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs of invasion may include a palpable component and dermoscopic features such as milky pink or blue-grey structureless areas, chrysalis structures (white streaks) and polymorphous vessels ( Figure 1). 2,3 Importantly, some melanomas (nodular and desmoplastic subtypes in particular) may be pink or skin-coloured and relatively featureless ( Figure 2). 2,4 An individual's underlying risk should be considered when assessing lesions of concern and tailoring surveillance.…”
Section: Diagnosismentioning
confidence: 99%